2021
DOI: 10.1002/mabi.202100202
|View full text |Cite
|
Sign up to set email alerts
|

Lollipop‐Inspired Multilayered Drug Delivery Hydrogel for Dual Effective, Long‐Term, and NIR‐Defined Glaucoma Treatment

Abstract: Glaucoma is an ophthalmic disease that is characterized by elevated intraocular pressure (IOP). Eye drops are the preferred choice to reduce IOP for the treatment of glaucoma. However, the bioavailability of eye drops is low (<5%). Their long‐term frequent administration cannot ensure patient compliance, which is the main reason for treatment failure. Inspired by lollipop, herein, a multilayered sodium alginate‐chitosan (SA‐CS) hydrogel ball (HB) decorated by zinc oxide‐modified biochar (ZnO‐BC) is developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It is noted that the tensile strength of traditional chitosan hydrogel formed by base neutralization is in the range of 0.1–1.25 MPa. 21–23 We also found that prolonging the deposition time from 1 to 3 h increased the toughness of the hydrogel tubes. As shown in Fig.…”
mentioning
confidence: 63%
“…It is noted that the tensile strength of traditional chitosan hydrogel formed by base neutralization is in the range of 0.1–1.25 MPa. 21–23 We also found that prolonging the deposition time from 1 to 3 h increased the toughness of the hydrogel tubes. As shown in Fig.…”
mentioning
confidence: 63%
“…Thus, in this work, the polydopamine-based microgels are expected to improve the drug bioavailability by improving ocular surface adhesion and retention. Accordingly, undesired side effects of MCC950 can be avoided by reducing the dosage ( Wang F. et al, 2021 ). Herein, the ocular surface retention was evaluated by detecting the concentration of FS in tear samples after topical treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are many drugs for relieving or treating eye in drops, powders and ointments on the market, there are many deficiencies in their use, such as low permeability, low bioavailability, short stay time, frequent administration, etc. The intraocular bioavailability of these drugs is very low, usually only 1–5% ( Wang F. et al, 2021 ). At present, some non-traditional ocular drug delivery systems have been extensively studied, such as nano carriers, hydrogels, liposomes, etc.…”
Section: Biomedical Applications Of Photothermal Nanocomposite Hydrogelsmentioning
confidence: 99%